A Tale of Two Regions: An Analysis of Two Decades of Belgian Public Opinion. Issue 4 (10th November 2021) - Hooghe, Marc; Stiers, Dieter
Abstract: It has been assumed that a trend toward devolution within a federal country would be associated with a growing apart of public opinion, and the federal kingdom of Belgium is routinely cited as an obvious example in this regard. Since the publication of the seminal Billiet et al. article, more competences have been devolved toward the autonomous regions, and in this research note we update the expectation that this has led to a further growing apart of public opinion in the country. Based on both electoral studies (2009/2014/2019), and the European Social Survey (2002–2018) we investigate whether these institutional differences are associated with a growing apart of public opinion in the regions of Belgium. Our results suggest that while there are clear attitudinal differences between the two major groups in the country, these differences are stable throughout the three-decade observation period. Differences are becoming more outspoken, however, with regard to the preferred extent of federalism. Interestingly, however, the dynamics in public opinion in this regard do not follow the same pattern as electoral results would suggest.